Perceptions of stigma toward mental illness in Arab society in Israel. (May 2023) - Fahoum, Kholoud; Al-Krenawi, Alean
Stigma is a major obstacle for people diagnosed with mental illness and this impacts the burden of the disease. This study compares the relationship between personal and social stigma in patients diagnosed with mental illness in two distinct Arab communities: the Bedouin in the Negev Desert in Israel and the Arabs of East Jerusalem. The sample consisted of 140 participants. Research instruments measuring self-stigma, social stigma, and social support were deployed. Positive correlation between personal and social stigma was found. Personal stigma was higher among Bedouins, while social stigma was higher among East Jerusalem Arabs.